Os livros literários e a diversidade cultural na prática docente em artes visuais com crianças - Soares, Sâmela Jannie Ribeiro (2024)
The present study addressed the theme of pedagogical practices in art that incorporate literature as a resource for addressing cultural diversity in elementary school I. The objective was to demonstrate the importance of the literary book as a pedagogical tool for the art teacher, both by using written language and images, with a focus on practices and experiences lived with elementary school I classes in the municipal network of Uberlândia between 2019 and 2022. The methodology adopted was based on thematic analysis through bibliographic research, as well as the preparation of a report of the researcher's pedagogical practices as an art educator. The research focused on the interfaces between art, literature and cultural diversity, examining how the literary book can be used as a valuable tool to enrich art education and promote an inclusive and plural approach to cultural diversity. The results showed that the literary book constitutes an effective pedagogical resource, capable of awakening the interest and curiosity of students, as well as providing a more diverse and contextualized learning in art. The connection between art and literature allowed a rich and engaging approach to cultural diversity, contributing to a deeper and more empathetic understanding of the world and promoting respect and appreciation for cultural differences. In addition, the work resulted in the creation of a literary guide to cultural diversity and an online collection with titles of literature, reviews, and other information that aim to enrich pedagogical work in the field of cultural diversity. It was concluded that the experiences addressed in the study exemplify effective ways of working with cultural diversity in the classroom, valuing the experiences of students and using the literary book as a fundamental ally of pedagogical practices in art. The art educator has at his disposal a diverse range of resources that, if well used, can significantly contribute to the formation of individuals who are more aware, critical, and respectful of the cultural plurality that characterizes Brazilian society.